RANCANG BANGUN POWER STEERING HIDROLIK PADA TOYOTA KIJANG 5K: RANCANG BANGUN POWER STEERING HIDROLIK PADA TOYOTA KIJANG 5K - Ikhsan, Faiqul Rizaldy; Wijanarko, Diastian Vinaya (Jurnal Rekayasa Mesin, 2020)
The development of science and technology from year to year is increasing, where everything is made as efficient as possible. Various improvement efforts have been made in the automotive sector. Technological developments in the automotive sector play a major role in advances in other fields. Therefore it is necessary to have experts in the automotive field. To produce experts in the automotive sector, adequate facilities are needed as teaching materials. One of them is the facilities in the practicum, in the practicum, tools that are easy to understand and understand by the practitioner are needed. To make it easier to understand and understand how a tool works, it is not enough with theory, but it is necessary to have a practical tool that shows directly the components and how the tool works. This type of motorized vehicle / car is equipment that is needed in the industrialized world as a means of transportation, so it requires experts who are able to operate, maintain and repair the equipment. In today's motorized vehicles / cars, there are many very important systems, including the power steering system. Power steering functions as a tool to help soften or lighten the operation of the steering wheel, when the engine is on. Especially in hydraulic power steering works by utilizing the compressive power of liquid fluid, where the liquid fluid is pressurized by a pump. In a complete vehicle the hydraulic power steering components are not visible in their entirety. Some components are blocked or covered by other components, so it is quite difficult to learn them. Based on the above references, we will try to make a visual aid to overcome the limitations of the power steering hydraulic system practicum. We will raise an analysis of the design of hydraulic power steering props where the power steering to be used is the hydraulic power steering belonging to the Toyota Kijang. It is hoped that after this tool is completed, it can become a more effective learning tool for students, especially for students of mechanical engineering study programs for automotivespecialties. Keywords: Planning of Electric Motor Isuzu Panther VE Type Injection Pump Trainer